Pengaruh Komunikasi Terhadap Efektivitas Kerja Pegawai Pada Dinas Pekerjaan Umum Dan Bina Marga Kabupaten Sidrap - Nasriah Akil (Jurnal Online Manajemen ELPEI, 2022)
The purpose of conducting this research is to find out the power of influence of Communication on the Effectiveness of Work at the Public Works and Highways Office of Sidrap Regency. 25 respondents were taken as a sample. The research conducted by the researcher is a verification research or causality in nature, namely research that looks for the relationship between causal variables and effect variables. The relationship in question is the relationship between Communication (Independent variable) and Work Effectiveness (Dependent variable). The analytical tool used is the Spearman Rank coefficient formula (ρ) Based on the analysis of the collected data, the following conclusions can be drawn: 1) The results of the analysis show that Communication is associated with Work Effectiveness. This shows that the more effective the communication that occurs, the work effectiveness will increase, conversely if the communication is not effective then the work being done becomes even less effective. 2) Communication that occurs within the Public Works and Highways Office of Sidrap Regency is quite effective, because after all the role of the leadership here cannot be ruled out, because it is the leadership that creates pleasant environmental conditions or vice versa.